Nuclear localization of SMN and FUS is not altered in fibroblasts from patients with sporadic ALS - Kariya, Shingo (Amyotroph Lateral Scler Frontotemporal Degener, 2014)
BACKGROUND: Sporadic amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease with no established biological marker. Recent observation of a reduced number of gems (survival motor neuron protein (SMN)-positive nuclear bodies) in cells from patients with familial ALS and the mouse models suggests an involvement of SMN in ALS pathology. At a molecular level, fused in sarcoma (FUS), one of the familial ALS-linked proteins, has been demonstrated to directly interact with SMN, while impaired nuclear localization of mutated FUS causes defective gem formation. OBJECTIVE: To determine whether gems and/or nuclear FUS levels in skin derived-fibroblasts from sporadic ALS patients are consistently reduced and thus could constitute a novel and readily-available biomarker of the disease. METHODS: Fibroblasts from 20 patients and 17 age-matched healthy controls were cultured and co-immunostained for SMN and FUS. RESULTS: No difference was detected between two groups in the number of gems and in expression pattern of FUS. The number of gems negatively correlated with the age at biopsy in both ALS and control subjects. CONCLUSIONS: The expression pattern of SMN and FUS in fibroblasts cannot serve as a biomarker for sporadic ALS. Donor age-dependent gem reduction is a novel observation that links SMN with cellular senescence.